Antimicrobial peptides: Defending the mucosal epithelial barrier - Karen F. Johnstone; Mark C. Herzberg (Frontiers Media S.A., 2022)
The recent epidemic caused by aerosolized SARS-CoV-2 virus illustrates the importance and vulnerability of the mucosal epithelial barrier against infection. Antimicrobial proteins and peptides (AMPs) are key to the epithelial barrier, providing immunity against microbes. In primitive life forms, AMPs protect the integument and the gut against pathogenic microbes. AMPs have also evolved in humans and other mammals to enhance newer, complex innate and adaptive immunity to favor the persistence of commensals over pathogenic microbes. The canonical AMPs are helictical peptides that form lethal pores in microbial membranes. In higher life forms, this type of AMP is exemplified by the defensin family of AMPs. In epithelial tissues, defensins, and calprotectin (complex of S100A8 and S100A9) have evolved to work cooperatively. The mechanisms of action differ. Unlike defensins, calprotectin sequesters essential trace metals from microbes, which inhibits growth. This review focuses on defensins and calprotectin as AMPs that appear to work cooperatively to fortify the epithelial barrier against infection. The antimicrobial spectrum is broad with overlap between the two AMPs. In mice, experimental models highlight the contribution of both AMPs to candidiasis as a fungal infection and periodontitis resulting from bacterial dysbiosis. These AMPs appear to contribute to innate immunity in humans, protecting the commensal microflora and restricting the emergence of pathobionts and pathogens. A striking example in human innate immunity is that elevated serum calprotectin protects against neonatal sepsis. Calprotectin is also remarkable because of functional differences when localized in epithelial and neutrophil cytoplasm or released into the extracellular environment. In the cytoplasm, calprotectin appears to protect against invasive pathogens. Extracellularly, calprotectin can engage pathogen-recognition receptors to activate innate immune and proinflammatory mechanisms. In inflamed epithelial and other tissue spaces, calprotectin, DNA, and histones are released from degranulated neutrophils to form insoluble antimicrobial barriers termed neutrophil extracellular traps. Hence, calprotectin and other AMPs use several strategies to provide microbial control and stimulate innate immunity.